Overuse shoulder injuries in swimmers - Becker, T. J. (Journal of Swimming Research, 2011)
Shoulder injury is a significant barrier to the training regime and competition experience of the swimmer, both male and female. Both male and female swimmers have a unique potential for the onset of clinical shoulder symptoms. This review of shoulder symptom onset includes information related to growth, stroke biomechanics and signs and symptoms.